Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Variation in estimates of the footprint of large, ground-mounted photovoltaic solar energy in the United States and its associated land-cover change across three datasets - Michael O. Levin; Emma Forester; Elizabeth L. Kalies; Lauren Goodman; Jason S. Hagani; Chevon C. Holmes; Noah Z. Krasner; Caitlin Markus; Jared B. Meek; Anubhav Vanamamalai; Shivani Agarwal; Uzma Ashraf; et al. (Journal of Environmental Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Modeling and interpreting triple oxygen isotope variations in vertebrates, with implications for paleoclimate and paleoecology - Huanting Hu; Benjamin H. Passey; Sophie B. Lehmann; Naomi E. Levin; Beverly J. Johnson (Chemical Geology, 2023)

Fronto-striatal alterations correlate with apathy severity in behavioral variant frontotemporal dementia - Neeraj Upadhyay; Annika Spottke; Anja Schneider; Daniel C. Hoffmann; Ingo Frommann; Tommaso Ballarini; Klaus Fliessbach; Benjamin Bender; Hauke R. Heekeren; John Dylan Haynes; Michael Ewers; Emrah Düzel; et al. (Brain Imaging and Behavior, 2023)
Structural and functional changes in cortical and subcortical regions have been reported in behavioral variant frontotemporal dementia (bvFTD), however, a multimodal approach may provide deeper insights into the neural correlates of neuropsychiatric symptoms. In this multicenter study, we measured cortical thickness (CTh) and subcortical volumes to identify structural abnormalities in 37 bvFTD patients, and 37 age- and sex-matched healthy controls. For seed regions with significant structural changes, whole-brain functional connectivity (FC) was examined in a sub-cohort of N = 22 bvFTD and N = 22 matched control subjects to detect complementary alterations in brain network organization. To explore the functional significance of the observed structural and functional deviations, correlations with clinical and neuropsychological outcomes were tested where available. Significantly decreased CTh was observed in the bvFTD group in caudal middle frontal gyrus, left pars opercularis, bilateral superior frontal and bilateral middle temporal gyrus along with subcortical volume reductions in bilateral basal ganglia, thalamus, hippocampus, and amygdala. Resting-state functional magnetic resonance imaging showed decreased FC in bvFTD between: dorsal striatum and left caudal middle frontal gyrus; putamen and fronto-parietal regions; pallidum and cerebellum. Conversely, bvFTD showed increased FC between: left middle temporal gyrus and paracingulate gyrus; caudate nucleus and insula; amygdala and parahippocampal gyrus. Additionally, cortical thickness in caudal, lateral and superior frontal regions as well as caudate nucleus volume correlated negatively with apathy severity scores of the Neuropsychiatry Inventory Questionnaire. In conclusion, multimodal structural and functional imaging indicates that fronto-striatal regions have a considerable influence on the severity of apathy in bvFTD.

Triple oxygen isotope compositions of globally distributed soil carbonates record widespread evaporation of soil waters - Julia R. Kelson; Tyler E. Huth; Benjamin H. Passey; Naomi E. Levin; Sierra V. Petersen; Paolo Ballato; Emily J. Beverly; Daniel O. Breecker; Gregory D. Hoke; Adam M. Hudson; Haoyuan Ji; Alexis Licht; et al. (Geochimica et Cosmochimica Acta, 2023)

Task impairment: A novel approach for assessing impairment during exploration-class spaceflight missions - William Fernandez; Dana Levin; Jon G. Steller; Eric Kerstman; Jay Lemery; Christopher Zahner; Hillary E. Davis; Kris Lehnhardt; Benjamin Easter; Amy J. Kreykes (Journal of Space Safety Engineering, 2023)

Detecting hydrologic distinctions among Andean lakes using clumped and triple oxygen isotopes - Sarah A. Katz; Naomi E. Levin; Donald T. Rodbell; David P. Gillikin; Phoebe G. Aron; Benjamin H. Passey; Pedro M. Tapia; Analucía R. Serrepe; Mark B. Abbott (Earth and Planetary Science Letters, 2023)

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Ecometrics and the paleoecological implications of Pleistocene faunas from the western coastal plains of the Cape Floristic Region, South Africa - J. Tyler Faith; David R. Braun; Benjamin Davies; Larisa R. G. DeSantis; Matthew J. Douglass; Irene Esteban; Vincent Hare; Naomi E. Levin; Julie Luyt; Robyn Pickering; Mitchell J. Power; Judith Sealy; et al. (Journal of Quaternary Science, 2020)
The Pleistocene ungulate communities from the western coastal plains of South Africa's Cape Floristic Region (CFR) are diverse and dominated by grazers, in contrast to the region's Holocene and historical faunas, which are relatively species‐poor and dominated by small‐bodied browsers and mixed feeders. An expansion of grassy habitats is clearly implied by the Pleistocene faunas, but the presence of ruminant grazers that cannot survive the summer dry season typical of the region today suggests other important paleoecological changes. Here we use dental ecometrics to explore the paleoecological implications of the region's Pleistocene faunas. We show that the dental traits (hypsodonty and occlusal topography) of the ungulates that occurred historically in the CFR track annual and summer aridity, and we use these relationships to reconstruct past aridity. Our results indicate that the Pleistocene faunas signal paleoenvironments that were on average less arid than today, including during the summer, consistent with other lines of evidence that suggest a higher water table and expansion of well‐watered habitats. Greater water availability can be explained by lower temperature and reduced evapotranspiration during cooler phases of the Pleistocene, probably coupled with enhanced groundwater recharge due to increased winter precipitation.

FreeSurfer 5.3 versus 6.0: are volumes comparable? A Chronic Effects of Neurotrauma Consortium study - Erin D. Bigler; Marc Skiles; Benjamin S. C. Wade; Tracy J. Abildskov; Nick J. Tustison; Randall S. Scheibel; Mary R. Newsome; Andrew R. Mayer; James R. Stone; Brian A. Taylor; David F. Tate; William C. Walker; et al. (Brain Imaging and Behavior, 2020)

Influence of heme c attachment on heme conformation and potential - Jesse G. Kleingardner; Benjamin D. Levin; Giorgio Zoppellaro; K. Kristoffer Andersson; Sean J. Elliott; Kara L. Bren (JBIC Journal of Biological Inorganic Chemistry, 2018)

Exploring the Ecology of Deep-Sea Hydrothermal Vents in a Metacommunity Framework - Lauren S. Mullineaux; Anna Metaxas; Stace E. Beaulieu; Monika Bright; Sabine Gollner; Benjamin M. Grupe; Santiago Herrera; Julie B. Kellner; Lisa A. Levin; Satoshi Mitarai; Michael G. Neubert; Andreas M. Thurnherr; et al. (Frontiers in Marine Science, 2018)

Hydrothermal Vents and Methane Seeps: Rethinking the Sphere of Influence - Lisa A. Levin; Amy R. Baco; David A. Bowden; Ana Colaco; Erik E. Cordes; Marina R. Cunha; Amanda W. J. Demopoulos; Judith Gobin; Benjamin M. Grupe; Jennifer Le; Anna Metaxas; Amanda N. Netburn; et al. (Frontiers in Marine Science, 2016)

The social benefits of private infectious disease-risk mitigation - Benjamin R. Morin; Charles Perrings; Ann Kinzig; Simon Levin (Theoretical Ecology, 2015)

Methane seep ecosystem functions and services from a recently discovered southern California seep - Benjamin M. Grupe; Monika L. Krach; Alexis L. Pasulka; Jillian M. Maloney; Lisa A. Levin; Christina A. Frieder (Marine Ecology, 2015)
The recent discovery of a methane seep with diverse microhabitats and abundant groundfish in the San Diego Trough (1020 m) off the coast of Del Mar, California raised questions about the role of seep ecosystem functions and services in relation to continental margins. We used multicorer and ROV grab samples and an ROV survey to characterize macrofaunal structure, diversity, and trophic patterns in soft sediments and authigenic carbonates; seep microhabitats and taxa observed; and the abundance and spatial patterns of fishery‐relevant species. Biogenic microhabitats near the Del Mar Seep included microbially precipitated carbonate boulders, bacterial mats, vesicomyid clam beds, frenulate and ampharetid beds, vestimentiferan tubeworm clumps, and fields of Bathysiphon filiformis tubes. Macrofaunal abundance increased and mean faunal δ 13 C signatures decreased in multicorer samples nearer the seep, suggesting that chemosynthetic production enhanced animal densities outside the seep center. Polychaetes dominated sediments, and ampharetids became especially abundant near microbial mats, while gastropods, hydroids, and sponges dominated carbonate rocks. A wide range of stable isotopic signatures reflected the diversity of microhabitats, and methane‐derived carbon was the most prevalent source of nutrition for several taxa, especially those associated with carbonates. Megafaunal species living near the seep included longspine thornyhead ( Sebastolobus altivelis ), Pacific dover sole ( Microstomus pacificus ), and lithodid crabs ( Paralomis verrilli ), which represent targets for demersal fisheries. Sebastolobus altivelis was especially abundant (6.5–8.2 fish·100 m −2 ) and appeared to aggregate near the most active seep microhabitats. The Del Mar Methane Seep, like many others along the world's continental margins, exhibits diverse ecosystem functions and enhances regional diversity. Seeps such as this one may also contribute ecosystem services if they provide habitat for fishery species, export production to support margin food webs, and serve as sinks for methane‐derived carbon.

Gene–environment interactions between JAZF1 and occupational and household lead exposure in prostate cancer among African American men - Christine Neslund-Dudas; Albert M. Levin; Jennifer L. Beebe-Dimmer; Cathryn H. Bock; Nora L. Nock; Andrew Rundle; Michelle Jankowski; Richard Krajenta; Q. Ping Dou; Bharati Mitra; Deliang Tang; Timothy R. Rebbeck; et al. (Cancer Causes & Control, 2014)

Growth line deposition and variability in growth of two circumpolar bivalves (Serripes groenlandicus, and Clinocardium ciliatum) - William G. Ambrose; Paul E. Renaud; William L. Locke; Finlo R. Cottier; Jørgen Berge; Michael L. Carroll; Benjamin Levin; Stuart Ryan (Polar Biology, 2012)

Results from a prostate cancer admixture mapping study in African-American men - Cathryn Hufford Bock; Ann G. Schwartz; Julie J. Ruterbusch; Albert M. Levin; Christine Neslund-Dudas; Susan J. Land; Angela S. Wenzlaff; David Reich; Paul McKeigue; Wei Chen; Elisabeth I. Heath; Isaac J. Powell; et al. (Human Genetics, 2009)

A simple plant regeneration-ability assay in a range of Lycopersicon species - Benjamin Steinitz; Anat Amitay; Victor Gaba; Yona Tabib; Menachem Keller; Ilan Levin (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)